Non-Authentic Property Declaring as a Qualifying Feature of a Corruption Offense: The Experience of Eu Countries - Akimov, Mykhailo O.; Kholostenko, Andrii V.; Yavorska, Iryna M.; Dragan, Olena V.; Burak, Stepan V. (International Journal of Criminology and Sociology, 2022)
Declaring property is a method of fighting and preventing corruption. Making it mandatory to provide information about the property causes a number of problems that are related to the inaccuracy of the declaration information. European Union (EU) countries have different approaches to providing information and property information. Significant differences in the requirements for declaring income and assets were revealed. It was done on the basis of the data analysis. The systems of declaration and verification of information on the property of Central and Eastern European (CEE) countries were studied in this work. The difference in the procedures of verification of authenticity and establishment of responsibility in case of detection of violation is determined. It is determined that smaller sanctions have been imposed in the countries of Central and Eastern Europe with a higher level of corruption. Sanctions mainly relate to the imposition of fines. In Greece, penalties for administrative fines vary considerably in the number of fines and, in some cases, it might be imprisonment for up to 10 years. The system of verification of declarations also varies significantly within Central and Eastern Europe: from verification of declarations, in particular randomly or automatically, the usage of risk assessment methodology for inaccurate information of the declarant to the notification of unjustified amount of property. It is determined that the inspection takes place as a result of bringing a person to justice in 6 countries.